2023
DOI: 10.3847/1538-4357/ad05c9
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Decay of Hot Jupiters due to Weakly Nonlinear Tidal Dissipation

Nevin N. Weinberg,
Niyousha Davachi,
Reed Essick
et al.

Abstract: We study tidal dissipation in hot Jupiter host stars due to the nonlinear damping of tidally driven g-modes, extending the calculations of Essick & Weinberg to a wide variety of stellar host types. This process causes the planet’s orbit to decay and has potentially important consequences for the evolution and fate of hot Jupiters. Previous studies either only accounted for linear dissipation processes or assumed that the resonantly excited primary mode becomes strongly nonlinear and breaks as it approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…However, at the shortest orbital periods (<5 days), even planets around evolved stars appear to have largely circular orbits. Constraints on orbital eccentricities will constrain both planet engulfment and stellar structure models (Weinberg et al 2017;Sun et al 2018;Soares-Furtado et al 2021;Grunblatt et al 2023;Weinberg et al 2024). We find no evidence for significant eccentricity in the orbit of TIC 365102760 b based on our current set of observations.…”
Section: Radial Velocitymentioning
confidence: 57%
“…However, at the shortest orbital periods (<5 days), even planets around evolved stars appear to have largely circular orbits. Constraints on orbital eccentricities will constrain both planet engulfment and stellar structure models (Weinberg et al 2017;Sun et al 2018;Soares-Furtado et al 2021;Grunblatt et al 2023;Weinberg et al 2024). We find no evidence for significant eccentricity in the orbit of TIC 365102760 b based on our current set of observations.…”
Section: Radial Velocitymentioning
confidence: 57%
“…The orbital period decrease for this planet was measured as P 131 22  =  ms yr −1 by Vissapragada et al (2022). The evolved host star is probably key to explaining the rapid rate of decay: although Weinberg et al (2024) found that g-mode dissipation is too weak to explain it, Vissapragada et al (2022) argued that inertial wave dissipation, combined with rapid stellar rotation, could. On the other hand, recent results from Barker et al (2024) find that the time the star spends with Q 10 4  ¢ < may be too short, potentially requiring nonsynchronous rotation if tidal dissipation is to explain the rate of orbital decrease.…”
Section: Kepler-1658 B: Existing Data Have Promising δBicmentioning
confidence: 99%
“…The resulting theoretical estimates for Q  ¢ are listed as Q th ¢ in Table 3, and we computed the theoretical decay time τ th and rate of period decrease P th  as in Equation (15) in Weinberg et al (2024). For stellar models with radiative cores and convective envelopes, Weinberg et al (2024) found values that range from Q 10 th 5…”
Section: Comparison To Theorymentioning
confidence: 99%
“…The full calculation of k abb¢ is challenging (e.g., Van Beeck et al 2023). For a ∼4 Gyr solar-mass star, using the WKB scaling for how parent and child modes behave close to the star's center, Weinberg et al (2012Weinberg et al ( , 2024 show that k abb¢ may be approximated as E E thr,sw , which does not depend on Δ α . To demonstrate how parametric instability and the spawning of child modes can suppress the resonant response of the parent, we solve Equations (B1) using the following model.…”
Section: B1 Nonlinear Breaking Of the Three-mode Parametric Instabilitymentioning
confidence: 99%